Classroom Action Research: Using the Tikrar Method to Improve Competency in Memorizing the Quran - Oktavia, Virza; Zulmasri, Zulmasri; Nurhayati, Nurhayati; Fauzana Azima, Nana; Ariyanti, Dhyan; Jaili, Hambali (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Learning methods are one of the determining factors in achieving student learning competency. With the right method, the competencies expected in learning become easier to achieve. This also applies to learning Islamic Religious Education in elementary schools. One effective method that can be used for learning the Quran and Hadith material is the Tikrar method. This research aims to analyze the effect of using the Tikrar method in improving elementary school students' ability to memorize the Quran. This research uses a Classroom Action Research design with two cycles, which was carried out in one elementary school in Indonesia. Research data was taken from teachers and nineteen students, with data collection techniques through observation and tests. Data were analyzed using SPSS 21 and qualitative descriptive analysis. The research results showed a significant increase in students' memorization competence, where the cumulative daily test scores increased from 45% to 94.74%. These findings prove that the Tikrar method is effective in improving students' memorization abilities in the Quran and Hadith subjects in elementary schools.